OR06-02 TBR-760, a Chimeric Somatostatin-Dopamine Compound, Arrests Aggressive Non-Functioning Pituitary Adenoma Growth In Vivo - Halem, Heather A (J Endocr Soc, 2020)
TBR-760 is a chimeric dopamine (DA)-somatostatin (SST) compound with potent agonist activity at both DA type 2 (D2R; EC(50) 0.064nM) and SST type 2 (SSTR2; EC(50) 1.2nM) receptors. Prior studies have demonstrated that the chimeric DA-SST compounds are more potent and effective than either individual or combinations of individual DA and/or SST analogs in inhibiting secretion from pituitary adenomas. Non-functioning pituitary adenomas (NFPA) express high levels of D2R as well as lower levels of SSTRs, including the type 2 receptor (1), and thus have an appropriate receptor profile to respond to TBR-760. The present study examines the ability of TBR-760 to inhibit tumor growth in a mouse model of aggressive NFPA. Heterozygous and null mutant mice lacking one or both copies, respectively, of the pro-opiomelanocortin (POMC) gene (POMC-KO mice)(2) spontaneously develop aggressive, non-secreting pituitary adenomas (3). The POMC-KO mouse tumors have been shown to express D2R and SSTR2 at a similar level as human NFPAs (4). In addition, merging of microarray data (Affymetrix, U133 plus_2.0 and Mouse Genome 430 2.0 arrays), reveals 154 common gene signatures between human NFPAs and the POMC-KO mouse tumors. In an initial study, heterozygous POMC-KO mice with an established pituitary tumor of approx. 10mm(3) (mean volume 8.9±0.3), as determined by MRI, were treated with a range of TBR-760 doses (0.125 to 12.5mg/kg, sc, QD) for 60 days. During that time, tumors in vehicle-treated mice increased in size by 890±0.7%, whereas all doses of TBR-760 tested resulted in a nearly complete inhibition of tumor growth from treatment initiation. We then compared the effect of the TBR-760 chimera with that of its individual SST agonist (SSTA) and DA agonist (DAA) components on tumor growth in the POMC-KO mice. As in the earlier study, TBR-760 treatment (1mg/kg, sc, QD), initiated when the mice had an established tumor of approx. 10mm(3), completely arrested tumor growth during the 8 weeks of treatment (final mean tumor volume of 8.5±1.3mm(3) vs. 54.61±10.6mm(3) in vehicle-treated mice). Treatment with equimolar or 10x-higher doses of the individual SSTA or DAA, either alone or in combination, had no significant effect on tumor growth, except in the lower dose DAA group where a modest suppression of tumor growth was observed. These data demonstrate that only the dual DA-SST chimeric compound, TBR-760, completely arrested tumor growth in the POMC-KO mouse model of NFPA. Further, despite the highly aggressive nature of the POMC-KO tumors, significant tumor shrinkage was observed in 20% of the mice treated with TBR-760. These results support the development of TBR-760 as a medical therapy to prevent or arrest the growth of NFPAs and, potentially, to induce NFPA shrinkage. References: (1) Florio et al., 2008 Endocr Relat Cancer; 15: 583-596. (2) Yaswen et al., 1999 Nat Med; 9:1066-70 (3) Karpac J et al., 2006 Cell Mol Biol; 52: 47-52.